Capturing School Data on Bullying and Harassment is Just the Beginning of the Story, Using the Data Can Provide Us with an Ending - Anne DeVivio Mary (Journal of Human Psychology, 2023)
This article argues that collecting school data on bullying and harassment must be paired with transparent analysis and targeted interventions. It outlines governance, feedback loops, and practical steps to translate data into safer environments.